Personality development and intellectual disability. Issue 1 (January 2015) - Roy, Meera; Retzer, Ameeta; Sikabofori, Tonye
Abstract : Purpose of review: This review examines the factors that shape personality and how they can inform on the behaviour of people with intellectual disability both to help them function at least at their cognitive level and add a developmental dimension to treatment plans. Recent findings: People with intellectual disability experience more failure, rejection and social deprivation leading to personality traits that may impede their ability to learn and predispose them to depression. Brain changes due to genetic conditions may be responsible for the behavioural phenotypes, although the autism phenotype is associated with different causes. Schizophrenia has a strong neurodevelopmental component and it could be on a gradient of decreasing neurodevelopmental impairment between intellectual disability and autism on one hand and bipolar disorder on the other. Summary: Understanding how early-life experience and current-life situations give rise to personality traits and taking a developmental perspective, for example, mental age, could clarify the clinical presentation. Developments in molecular genetics and brain imaging may clarify how brain changes lead to personality features. Finally, it may be time to address whether it is still helpful to have categorical diagnoses when there is increasing evidence from genetic studies supporting a continuum of neurodevelopmental disorders.